Freshwater microbial community diversity in a rapidly changing High Arctic watershed. Issue 11 (10th October 2019) - Cavaco, Maria Antonia; St. Louis, Vincent Lawrence; Engel, Katja; St. Pierre, Kyra Alexandra; Schiff, Sherry Lin; Stibal, Marek; Neufeld, Josh David
ABSTRACT: Current models predict increases in High Arctic temperatures and precipitation that will have profound impacts on the Arctic hydrological cycle, including enhanced glacial melt and thawing of active layer soils. However, it remains uncertain how these changes will impact the structure of downstream resident freshwater microbial communities and ensuing microbially driven freshwater ecosystem services. Using the Lake Hazen watershed (Nunavut, Canada; 82°N, 71°W) as a sentinel system, we related microbial community composition (16S rRNA gene sequencing) to physicochemical parameters (e.g. dissolved oxygen and nutrients) over an annual hydrological cycle in three freshwater compartments within the watershed: (i) glacial rivers; (ii) active layer thaw-fed streams and waterbodies and (iii) Lake Hazen, into which (i) and (ii) drain. Microbial communities throughout these freshwater compartments were strongly interconnected, hydrologically, and often correlated with the presence of melt-sourced chemicals (e.g. dissolved inorganic carbon) as the melt season progressed. Within Lake Hazen itself, water column microbial communities were generally stable over spring and summer, despite fluctuating lake physicochemistry, indicating that these communities and the potential ecosystem services they provide therein may be resilient to environmental change. This work helps to establish a baseline understanding of how microbial communities and the ecosystem services they provide in Arctic watersheds might respond to future climate change. Abstract : High Arctic freshwater microbial communities are hydrologically interconnected over broad spatial scales throughout the Lake Hazen watershed (northern Ellesmere Island, Nunavut, Canada).